Aliarse (regionalmente) contra la Covid-19: Sica y Caricom - Parthenay, Kevin (El Colegio de México A.C., 2021)
The global health crisis linked to Covid-19 (SARS-Cov-2) has put all political systems around the world under strain, challenged economic and social systems and put international and regional organizations to the test. Although in Central America and the Caribbean, the member states of the Central American Integration System (Sica) and of Caricom respectively are characterized by fragility and vulnerability, the two regions report an astonishing performance in the management of the health crisis. Testing hypotheses relating to institutional learning, foreign aid and spatial distribution, we explain this apparent contradiction within the resilience in the face of the health crisis despite the weakness of regional state structures.